2021
DOI: 10.2503/hortj.utd-305
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Chalcones and their Contribution to Yellow Coloration in Dahlia (<i>Dahlia variabilis</i>) Ray Florets

Abstract: Yellow color in dahlia flowers is conferred from chalcones, butein and isoliquiritigenin. The color intensity of yellow dahlia cultivars is diverse, but a detailed study on this has not yet been performed. In this study, we first identified structures of flavonoids by nuclear magnetic resonance imaging in ray florets of the red-white bicolor 'Shukuhai', which contains chalcones, flavones and anthocyanins. Four anthocyanins, four flavone derivatives, five isoliquiritigenin derivatives and five butein derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…5D). To expand the experiment, we examined 21 more cultivars whose pigment composition was analyzed previously (Deguchi et al, 2013; Ohno et al, 2011a; 2011b; 2013b; 2021). Again, except for two cultivars (1: ‘Super Girl’ and 5: ‘Magokoro’), P1-P3 bands were detected from cultivars with butein but not from cultivars without butein (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…5D). To expand the experiment, we examined 21 more cultivars whose pigment composition was analyzed previously (Deguchi et al, 2013; Ohno et al, 2011a; 2011b; 2013b; 2021). Again, except for two cultivars (1: ‘Super Girl’ and 5: ‘Magokoro’), P1-P3 bands were detected from cultivars with butein but not from cultivars without butein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, flavonoids are accumulated as a glycoside in vivo , and dahlia accumulates isoliquiritigenin and butein as a 4′-glucoside or its derivatives (Harborne et al, 1990; Ohno et al, 2021). We assumed that tobacco plants are not able to accumulate isoliquiritigenin without glycosylation in vivo due to loss of suitable glucosyltransferase, thus, we tried to co-overexpress CHR (either DvCHR-1 , DvCHR-2 , GmCHR5 or GmCHR6 ) with a snapdragon chalcone 4′-glucosyltransferase ( Am4′CGT ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Desf. flow-ers (butein and isoliquiritigenin) [84,85]. Li et al [86], in their studies, reported that the edible flowers of Malus pumila Mill.…”
Section: Chalconesmentioning
confidence: 99%